Next-generation nutraceuticals: bioactive peptides from plant proteases - Fatema Matkawala; Sadhana Nighojkar; Anand Nighojkar (BioTechnologia, 2022)
Bioactive peptides are short and specific fragments of proteins with a wide range of biological activities that provide health benefits to the host. These natural peptides are safe and nontoxic and do not show any side effects. Nowadays, the production and characterization of bioactive peptides have been a key area of research as they show great potential as nutraceuticals and functional foods. Thus, bioactive peptides are considered next-generation therapeutic agents that can replace pharmaceutical products with profound adverse effects in the near future. So far, proteolytic hydrolysis has been used as the method of choice for the large-scale production of bio-active peptides. Studies have reported that peptides with specific characteristics can be generated using a particular type of protease. Microbial proteases are the predominantly used ones because of the ease in their production and purification. However, recently, plant proteases have gained a renewed interest as they offer diversity and better specificity compared with other proteases. This review highlights the potential of plant proteases for the production of bioactive peptides and also describes the benefits of bioactive peptides as nutraceuticals.